Leadership Coaching for Educators - Karla Reiss (Corwin Press, 2007)
There is an urgent need for school leaders to go beyond "top-down" supervision and coach educators to succeed. Use this comprehensive resource to design and implement an effective, school-wide coaching system that yields powerful results. Written by a veteran administrator and educational consultant, and aligned with the International Coach Federation’s Professional Coaching Core Competencies, this revised edition demystifies the coaching process